Annotated Bibliography Perpustakaan Tun Abdul Razak Issue 2/2018 - Jabatan Pembangunan Bahan Perpustakaan, Bahagian Pemprosesan Teknikal (Perpustakaan Tun Abdul Razak, 2018)
The Annotated Bibliography Perpustakaan Tun Abdul Razak UNIVERSITI TEKNOLOGI MARA SHAH ALAM is a list of library materials added into the collection of Perpustakaan Tun Abdul Razak in Shah Alam Campus. It will be published quaterly (4 issues a year). The listed materials are available in various formats obtained through the procurement process including donation.